Gestión de mantenimiento centrado en la confiabilidad operacional en camiones eléctricos Hitachi EH 5000 de 320T para la compañía minera a cielo abierto Cerrejón (2021)
This degree work has been dedicated to maintenance management focused on operational reliability in HITACHI EH 5000 320T electric trucks for the open pit mining company Cerrejón. For the development of the present work, the operating parameters and the current maintenance indicators of the HITACHI EH 5000 DE 320 equipment were described. Subsequently, the criticality analysis, root cause, Pareto diagram of the failures and the mode and effect analysis were carried out. of the fault. Finally, the maintenance processes and standard work procedures are established. The development of the work was framed in a study period of one calendar year for this case the year 2020, time that allowed taking relevant data for the analysis and subsequently obtaining the results. The reliability of the CAM 320T fleet was determined to average 98.3%, that the TPPR is 3.42 h / failure and that the TPEF is 64.47 h / failure. Applying maintenance management to the CAM 320 fleet made it possible to identify frequent failures and analyze them in detail to use continuous improvement tools and improve the processes that were standardized